Uniting in Humanity: The Role of Indonesian Red Cross 1870-1960 - Indra Fibiona; Siska Nurazizah Lestari; Ahmad Muhajir (IHiS (Indonesian Historical Studies), 2020)
The Red Cross is an important organization engaged in the humanitarian field. Red Cross had a long history regarding its important contributions among national movement to the Indonesian Revolution period. The history of the Red Cross from Bataviaasch Comite to be the Indonesian Red Cross (PMI) was very complex, due to many dynamics and chronicles in it. There were lots of interesting problems to study on the Red Cross transition from the colonial government to the Republic of the Indonesia government. Based on the reason above, this research discusses the Red Cross transformation from the Bataviaasch Committee into the Indonesian Red Cross (PMI). The research was historical research by applying four stages. Analysis results indicated that Red Cross's development from Bataviaasch Committee to PMI had many obstacles, both internal and external ones. Moreover, political constellation at that time also gave a great effect on Indonesian Red Cross development. However, these uncertain conditions have confirmed the Indonesian Red Cross establishing process.